Analisis Penambangan Galian Golongan C di Nagari Surantih Kecamatan Sutera Kabupaten Pesisir Selatan - Dike Armita; Nefilinda Nefilinda; Yuherman Yuherman (Journal on Education, 2023)
The purpose of this study is to analyze and describe (1) mining activities, (2) the impact of mining on the community's environment, (3) the impact of mining on the community's economy. The type of research used is descriptive qualitative, namely research that functions to see, reveal and describe the Analysis of Group C Quarry Mining in Kenagarian Surantih, Sutera District, Pesisir Selatan Regency. The analysis technique used is purposive sampling, which is a data collection technique by determining the sample with certain considerations, which is carried out together with data collection. The results of the study (1) Class C quarry mining activities in Kenagarian Surantih 73.1% are in the good category, C quarry mining activities in Kenagarian Surantih are illegal mining using traditional methods, (2) the impact of mining on the environment of the community in Kenagarian Surantih 61.1% is in the good category, the impact of mining on the environment is the occurrence of damage to community land that is on the banks of the river, and there is damage to roads caused by group C excavation transport trucks, 3) the impact of mining on the community's economy 82, 1% is in the very good category, namely increasing people's income, increasing income, and reducing unemployment